Specificity of S fimbriae on recombinant Escherichia coli: preferential binding to gangliosides expressing NeuGc alpha (2-3)Gal and NeuAc alpha (2-8)NeuAc. - Hanisch, F G (1993)
The adhesins of Escherichia coli strains HB101(pANN801-13) and HB101(pAZZ50), which express S fimbriae encoded by a recombinant plasmid containing the sfaI and sfaII gene clusters, respectively, were characterized with regard to the detailed structural requirements of their binding to sialyloligosaccharides on (neo)glycoproteins and (neo)glycolipids. From binding and binding inhibition studies in solid-phase enzyme immunoassays with isolated S fimbriae, several major conclusions can be drawn. S fimbriae bind specifically to sialic acid on gangliosides. The most active structural variant of sialic acid on GM3 ganglioside is N-glycolylneuraminic acid (NeuGc). In contrast to previous reports, high binding activities were measured also for b-series gangliosides expressing NeuAc alpha (2-8)NeuAc. In agreement with earlier studies, the site of sialic acid substitution to subterminal sugars strongly influences the binding to sialyloligosaccharides, i.e., alpha-6-linked sialic acid is only poorly recognized by the adhesin compared with alpha-3-linked sialic acid. C-8 and C-9 hydroxyl groups form essential structural elements of sialic acid in the binding event.